النوافذ الإسلامية في البنوك التقليدية: دراسة تحليلية على القضايا الشرعية وضوابط إنشائها: Islamic Windows in Traditional Banks: Analytical study on legitimate issues and its creation controls - Abu Hafiza, Suha Mufid; Che Abdullah, Ahmad Sufyan (Online Journal of Research in Islamic Studies, 2019)
The traditional banks work in the Islamic banking is considered one of the most prominent developments in the banking sector in the past years. So this study shed light on the traditional banks with Islamic windows. The study problem represents the traditional banks facilitation regarding work with the Islamic windows and the lack of commitment to Islamic Sharia. This study aims to demonstrate the legitimacy of work in the Islamic windows and invite banks to adhere to their legitimacy. The analytical inductive approach was used to understand the problems discussed in this study. This study revealed that the Islamic finance is the perfect and ideal solution which pushed banks to engage in the Islamic banking field. Therefore, this study recommends introducing Islamic banking; leaving usury funding and the partially or entirely shift of the traditional banks to Islamic windows which will reflect positively on improving its work efficiency.